2008
DOI: 10.3892/or.20.1.135
|View full text |Cite
|
Sign up to set email alerts
|

Lentivirus-mediated short hairpin RNA targeting the APRIL gene suppresses the growth of pancreatic cancer cells in vitro and in vivo

Abstract: RNA interference (RNAi) is an evolutionarily conserved process of gene silencing in multiple organisms, which has become a powerful tool for investigating gene function by reverse genetics. Herein, we constructed a short hairpin RNA (shRNA) lentiviral expression vector targeting a proliferation-inducing ligand (APRIL) gene in the CFPAC-1 cell (a type of cell strain of human pancreatic cancer) in order to observe the inhibitory effect of APRIL gene's shRNA on the growth of the CFPAC-1 cell in vitro and in vivo.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…However, downstream signaling cascades activated by APRIL that may be involved in tumor formation have yet to be characterized. We recently confirmed that APRIL is overexpressed in digestive system carcinomas, specifically in the colon and pancreas [13], [14], [15]. APRIL is more highly expressed in tumors than in normal colon, and APRIL-knockdown inhibited the migration and invasion of colorectal cancer cells in vitro [16].…”
Section: Introductionmentioning
confidence: 60%
“…However, downstream signaling cascades activated by APRIL that may be involved in tumor formation have yet to be characterized. We recently confirmed that APRIL is overexpressed in digestive system carcinomas, specifically in the colon and pancreas [13], [14], [15]. APRIL is more highly expressed in tumors than in normal colon, and APRIL-knockdown inhibited the migration and invasion of colorectal cancer cells in vitro [16].…”
Section: Introductionmentioning
confidence: 60%
“…In the case of TNFSF13, their role in cancer is not clear but other family members APRIL (a proliferation inducing ligand) and BAFF (B cell activating factor) play a role in chronic lymphocytic leukemia (CLL) [35] by increasing the survival of leukemic cells through blocking the apoptosis. The shRNA mediated blocking of APRIL The genes are grouped according to their cellular functions resulted in reduced growth of pancreatic tumour cells [46]. From our studies we observe an increase in 11E6 and a decrease in 18E6 compared to the mock.…”
Section: Transcription Regulationmentioning
confidence: 61%
“…However, studies have confirmed that it is overexpressed in many tumor tissues and many tumor cell lines, especially in the digestive system carcinomas, such as colon carcinoma, pancreatic cancer, gastric cancer, hepatoma and esophageal carcinoma, which suggests that APRIL has an important role in the occurrence and development of these tumors. [15][16][17][18][19] Our previous experiments have further confirmed that APRIL is overexpressed in CRC tumors, yet, it is not expressed or has a weak expression in normal colon mucosa tissues. Moreover, several CRC cell lines have been screened and it has been found that SW480 cell line is highly expressed in the APRIL gene.…”
Section: Introductionmentioning
confidence: 79%